View Single Post
Old 2017-02-03, 01:45   #3
Batalov
 
Batalov's Avatar
 
"Serge"
Mar 2008
Phi(4,2^7658614+1)/2

22×3×7×109 Posts
Default

Quote:
Originally Posted by carpetpool View Post
Help, comments, suggestions appreciated.

For three integers p, q, r such that gcd(p, q) = 1, gcd(r, q) = 1, let d = pr.

(p+q)*(q+d) - pq = x

(q+d)*q - p*(p+q) = y

Prove that

r*x-q-d = y
You can't prove that. It's false.

Take p,q,r = 2,5,3
d = p*r = 6
x=(p+q)*(q+d) - p*q = 67
y=(q+d)*q - p*(p+q) = 41
r*x-q-d = 190  \ne y
Batalov is offline   Reply With Quote